Nutrient dynamics in and offshore of two permanently open South African estuaries with contrasting fresh water inflow - Jennings, Michael Evan (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2006)
The nutrient dynamics in two contrasting estuaries and in the adjacent nearshore environment along the south-east coast of South Africa was investigated seasonally. Due to an inter-basin transfer of water from the Gariep Dam to the Great Fish River, the Great Fish estuary is a fresh water dominated, terrestrially driven system with an annual fresh water inflow of 250 "“ 650 x 10â ¶ mÂ³ per year. In contrast, the Kariega estuary is a fresh water deprived, marine dominated system with a fresh water inflow estimated at 2.5 "“ 35 x 10â ¶ mÂ³per year. The reduced fresh water inflow into the estuary is attributed to regular impoundments along the Kariega River. Water samples were collected from surface and subsurface layers along the length of the estuaries as well as from a series of transects occupied in the nearshore environment. Samples were analysed for nitrate, nitrite, ammonium, phosphate and silicate. Temperature and salinity were recorded at each station. A Land-Ocean Interactions in the Coastal Zone (LOICZ) budget was constructed for each estuary to describe the role of ecosystem-level metabolism as either a sink or a source of phosphorus, nitrogen and carbon. Seasonal variation in physico-chemical properties and nutrient concentrations in the Kariega estuary was minimal due to constant low inflow, while in the Great Fish estuary, concentrations varied in response to changes in flow rate. Nutrient concentrations were consistently higher in the Great Fish estuary than in the Kariega estuary, largely reflecting differences in fresh water inflow. During periods of high flow (32.92 mÂ³.sâ »Â¹in the Great Fish River) dissolved inorganic nitrogen (DIN) concentrations in the Great Fish estuary were an order of magnitude higher than those recorded in the Kariega estuary. Results of the LOICZ budgeting procedures revealed that in spite of the contrasting hydrodynamic features, the estuaries behave in largely the same manner "“ both predominantly sources of nutrients with heterotrophic processes dominating over autotrophic actions and both were net denitrifyers during all surveys. This was, however, due to different sets of processes operating in the two estuaries, namely low nutrient concentrations resulting in microbial activity in the Kariega estuary, and riverine influx of nutrients and phytoplankton combined with a short residence time of the water in the Great Fish estuary. In the marine nearshore environment, higher nutrient concentrations were recorded adjacent to the Great Fish estuary than offshore of the Kariega estuary. This was due to a surface plume of less saline water leaving the Great Fish estuary, which acted as an 'outweller' of nutrients. Offshore of the Kariega estuary, on the other hand, the nutrient concentrations were characteristic of marine waters due to a lack of fresh water outflow from the estuary. Nutrient concentrations in the marine environment adjacent to the Kariega estuary were, at times, higher than those recorded within the estuary. This observation supports previous statements which suggest that the Kariega estuary is not an 'outweller' of dissolved nutrients and particulate material, but rather an extension of the marine environment.
Keywords: Estuaries -- South Africa -- Great Fish River; Estuaries -- South Africa -- Kariega River; Marine ecology -- South Africa; Freshwater ecology -- South Africa; Rivers -- Environmental aspects; Water quality management -- South Africa; Water -- Analysis